Private military & security companies, conflict complexity, and peace duration: an empirical analysis. (16th November 2020) - Radziszewski, Elizabeth; Akcinaroglu, Seden
ABSTRACT: PMSC training has the potential to improve state capacity, reduce the combatants' opportunity and willingness to fight, and prolong the duration of peace. However, the benefit of PMSC training-related intervention over other types of PMSC interventions depends on the level of conflict complexity. Analysis of novel data on PMSC interventions and peace episodes following major/minor civil wars (1990–2008) shows that in cases when PMSCs intervene, training makes a positive contribution to peace in wars with a limited number of rebel groups that do not resort to terrorism. Positive impact dissipates in conflicts with greater levels of rebel fragmentation and terrorist tactics.